2011
DOI: 10.1093/cid/cir788
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Mycobacterium tuberculosis Phylogenetic Lineage and Clinical Site of Tuberculosis

Abstract: Phylogenetic lineage of M. tuberculosis is associated with the site of tuberculosis disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 20 publications
9
88
2
Order By: Relevance
“…Spoligotype and 12-locus MIRU-VNTR results were used to assign phylogenetic lineage, as described elsewhere. 26 To establish the likelihood of transmission in the USA, we classified cases on the basis of genotype, report date, and epidemiological link. Unlikely transmission was defined as cases of MDR tuberculosis with non-clustered genotypes reported in the same state (with or without extended typing data), and no epidemiological link.…”
Section: Methodsmentioning
confidence: 99%
“…Spoligotype and 12-locus MIRU-VNTR results were used to assign phylogenetic lineage, as described elsewhere. 26 To establish the likelihood of transmission in the USA, we classified cases on the basis of genotype, report date, and epidemiological link. Unlikely transmission was defined as cases of MDR tuberculosis with non-clustered genotypes reported in the same state (with or without extended typing data), and no epidemiological link.…”
Section: Methodsmentioning
confidence: 99%
“…Genotypic definitions-Four major phylogenetic lineages for M. tuberculosis [East African Indian, East Asian (i.e., Beijing strains), Euro-American, Indo-Oceanic], along with speciation of Mycobacterium africanum, were assigned using a set of rules correlating spoligotype with lineages defined by large sequence polymorphisms (LSP) (Click et al, 2012b;Supply et al, 2006). In cases that did not meet the full requirement for phylogenetic lineage assignment based on spoligotype, 12-locus MIRU-VNTR results was used in addition to spoligotype to assign lineage, as described elsewhere (Click et al, 2012b;Shabbeer et al, 2012). We excluded patients with M. africanum or Mycobacterium bovis isolates.…”
Section: Genotyping Methodsmentioning
confidence: 99%
“…However, we and others have demonstrated that the various lineages and sublineages of M.tb have distinct clinical and epidemiological phenotypes, including their pathogenicity (11,(39)(40)(41)(42). If bacterial factors associated with pathogenicity are found, it may be possible in the future to determine which patients are more likely to transmit and cause secondary cases among their contacts, enabling implementation of specific strategies directed toward these contacts.…”
Section: Policy Implicationsmentioning
confidence: 97%